Hubungan Faktor Beban Kerja Terhadap Burn Out Syndrome Tenaga Kesehatan Dalam Penanganan Pandemi Covid Di Asia: Meta Analysis - Hardiani W, Rr. Ambar; Hartono, Risky Kusuma (Syntax Corporation, 2025)
This study aims to analyze the relationship between workload factors and the occurrence of Burnout Syndrome among healthcare workers involved in managing the Covid-19 pandemic in Asia through a meta-analysis approach. A systematic review method was applied using inclusion criteria that consisted of studies examining the effect of workload on Burnout Syndrome among healthcare workers with a cross-sectional design, written in English or Indonesian, and conducted between 2019 and 2021. Data were collected from various databases and analyzed using R Studio software, with the assistance of an effect size converter and JAMOVI to test correlation and regression among variables. The results revealed a significant relationship between increased workload and the incidence of Burnout Syndrome among healthcare workers in Asia during the Covid-19 pandemic. Furthermore, the funnel plot and Egger’s test confirmed that publication bias did not affect the strength of the relationship between variables. These findings highlight the importance of workload management and psychosocial support for healthcare professionals to mitigate mental health risks during global health crises.